Agile methods as stress management tools? an empirical study. (1st January 2019) - Pfeiffer, Sabine; Sauer, Stefan; Ritter, Tobias
Abstract : Project-based work is considered a prototype for modern knowledge work, but is also often linked to stress. Complementing or substituting for conventional project management, agile methods are on the rise, but the implications of these methods for stress on employees still remain largely hidden. This article presents the results from qualitative case studies in software development that show how diverse agile methods are lived in practice and how these variations affect stress levels. The results unveil how agile methods, under certain assumptions, can protect team members against stress and voluntary self-exploitation - offering a safe space that is, however, fragile and requires accompanying organisational backing.